Bullying at work and onset of a major depressive episode among Danish female eldercare workers - Rugulies, Reiner; Madsen, Ida EH; Hjarsbech, Pernille U; Hogh, Annie; Borg, Vilhelm; Carneiro, Isabella G; Aust, Birgit (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVE ': 'The aim of this study was to analyze whether exposure to workplace bullying among 5701 female employees in the Danish eldercare sector increases the risk of onset of a major depressive episode (MDE). ' ' METHODS ': 'Participants received questionnaires in 2004–2005 and again in 2006–2007. MDE was assessed with the Major Depression Inventory. We examined baseline bullying as a predictor of onset of MDE at follow-up using multiple logistic regression. We further conducted a cross-sectional analysis at the time of follow-up among participants who at baseline were free of bullying, MDE, and signs of reduced psychological health. Finally, we analyzed reciprocal effects, by using baseline bullying and baseline MDE as predictors for bullying and MDE at follow-up. ' ' RESULTS ': 'Onset rates of MDE in the groups of no, occasional, and frequent bullying were 1.5%, 3.4%, and 11.3%, respectively. Odds ratios (OR) for onset of MDE were 2.22 [95% confidence interval (95% CI) 1.31–3.76] for occasional bullying and OR 8.45 (95% CI 4.04–17.70) for frequent bullying, after adjustment for covariates. In the cross-sectional analysis, OR were 6.29 (95% CI 2.52–15.68) for occasional bullying and 20.96 (95% CI 5.80–75.80) for frequent bullying. In the analyses on reciprocal effects, both baseline bullying [occasional: OR 2.12 (95% CI 1.29–3.48) and frequent: OR 6.39 (95% CI 3.10–13.17)] and baseline MDE [OR 7.18 (95% CI 3.60–14.30] predicted MDE at follow-up. However, only baseline bullying [occasional: OR 7.44 (95% CI 5.94–9.31) and frequent: OR 11.91 (95% CI 7.56–18.77)] but not baseline MDE [OR 0.93 (95% CI 0.47–1.84)] predicted bullying at follow-up. ' ' CONCLUSIONS ': 'Workplace bullying increased the risk of MDE among female eldercare workers. MDE did not predict risk of bullying. Eliminating bullying at work may be an important contribution to the prevention of MDE.
Keywords: anxiety; bullying; Denmark; depression; depressive episode; eldercare worker; healthcare worker; longitudinal study; major depressive episode; mental health; negative act; occupational health; psychosocial factor; stress; workplace bullying